Economic status and leisure time as indices of recreational sports participation among selected members of Ibadan recreation club, Ibadan, Nigeria (2016)
The recent emphasis on well-being of corporate employees and every individual may not be unconnected with the problems of global prevalence of physical inactivity, causing millions of death worldwide and Nigeria is not an exception. Consequently, recreation has been recognized as the most identified remedy to the problems of physical inactivity and other health related problems brought about by daily exigencies among the general public, especially corporate employees. Therefore, this study was embarked upon to investigate economic status and leisure time as indices of recreational sports participation among selected members of Ibadan Recreation Club, Ibadan, Nigeria. Two hundred (200) (58%) regular participants were purposively selected from the total of three hundred and fifty (350) registered members. Self- developed, structured and validated questionnaire with reliability coefficient of 0.87 was used to generate data. The questionnaire was analyzed using inferential statistics of chi-square (2) of contingency table to test the hypotheses at 0.05 levels of significance. The findings revealed that the two hypotheses tested were significant (2=247.4; p<0.05 and 2=30G.2;p<0.05). This implies that economic status and leisure-time highly influenced positively the participation in recreational sports among selected members of Ibadan Recreation Club, Ibadan, Nigeria. The study concluded with some recommendations in anticipation that if implemented, may help to encourage and promote affordable recreation opportunities for mass participation in recreational sports activities for healthy living.